Nutrient Composition of Traditional Foods and Their Contribution to Energy and Nutrient Intakes of Children and Women in Rural Households in Igbo Culture Area - Eneobong, H.N.; Okeke, E.C.; Uzuegbunam, A.O.; Ozioko, A.O.; Umeh, S.I.; Kuhnlein, H. (Pakistan Journal of Nutrition, 2009)
Micronutrient deficiency, namely: vitamin A, iron, iodine, zinc and burden of chronic diseases are prevalent. Eight communities selected from four States were used for this study. Key informant interviews, focus group discussions, nutrient composition and food intakes were used to ascertain use of local foods by households. Nutrient analysis on food recipes was carried out for all dishes collected from the field survey. Two communities out of the eight were randomly selected for detailed weighed food intake study which was done on a sub-sample to determine contribution of traditional foods. Results revealed that most of the recipes had reasonable energy content, at least over 90% of the energy was contributed to the diet of respondents from traditional foods. Moisture content was high and ranged from 44.3% in bambara fufu to 76% in palm nut soup/sauces. Protein content ranged from 0.2% in dried cassava fufu to 14.6% in plain bambara fufu. The recipes had reasonable nutrient content but were low in the micronutrients that were of public health importance, namely; iron, zinc and folic acid. Intakes of fruits and vegetables were low in these communities. In Anambra State, nuts and seeds made substantial contribution to energy, protein, calcium and iron while in Enugu State, legumes and cereals contributed to energy, protein, calcium and iron intakes. Further more, the bulk of the ascorbic acid came from vegetables in Anambra State (34-62%) while in Enugu State the ascorbic acid came from starchy roots and tubers (51-58%). The red palm oil (RPO) used in preparing many traditional dishes was the major source of vitamin A in the diet of the Igbo culture area. It contributed 70 - 85% of the vitamin A. Although traditional foods/diet made substantial contribution to the nutrient intakes of the populations studied, the results showed that in almost all the age groups low intakes of energy, calcium, riboflavin and niacin were observed. Low intakes were recorded more for children 6 - 12 years of age. Interventions to solve these problems must consider these issues in order to make a significant impact.